Design of an Application System for Creative Recording of Students at SMK N 9 Medan Based on Android - Hafni; Irwan; Zen, Muhammad; Rizki, Muhammad (Bahasa Indonesia, 2024)
A school is an institution or agency to create a means of activities for students' learning media and teaching for educators formed in an organization. One of the learning media that is developing in the future is creating brilliant creative ideas, so that it can provide motivation to students to create creative ideas. Creativity is a person's ability to create something new, either in the form of ideas or real works that are relatively different from what already exists. As for students' creative recording, it is still desktop-based. For this reason, a system needs to be developed so that it can provide information on creative students and non-creative students based on Android, in order to make it easier to manage and record students who are creative and not creative. By implementing an Android-based creative recording application for students, it is possible to optimize decision making in accordance with the provisions that have been set for processing student data for creative and non-creative students. Based on the results of system testing that has been implemented and is running optimally and can provide information about 90% of students who are creative and 10% of students who are not creative.